^{Solve algebraically : 3x^2/2=2(x-1)}

The first step would be to get rid of any denominators, so multiply both sides of the equation by 2 (what you do to one side of an equation you need to do to the other to maintain equality).

2*(3x^2)/2 = 2*(2(x-1)) and you get 3x^2 = 4(x-1)

Now get rid of the parentheses by distributing the 4 across the x-1 and you get

3x^2 = 4x-4

The next step is to put everything on the same side of the equation:

3x^2 -4x +4 =4x-4 - 4x+4

You now have 3x^2 -4x +4 =0

Hope this helps